New Delhi Metallo-Beta-Lactamase-Producing Enterobacteriaceae in South Korea Between 2010 and 2015 - Yoon, Eun-Jeong; Kang, Da Young; Yang, Ji Woo; Kim, Dokyun; Lee, Hyukmin; Lee, Kwang Jun; Jeong, Seok Hoon (Frontiers in Microbiology, 2018)
ABSTRACT This study was carried out to investigate the epidemiological time-course of New Delhi metallo-beta-lactamase- (NDM-) mediated carbapenem resistance in Enterobacteriaceae in South Korea. A total of 146 non-duplicate NDM-producing Enterobacteriaceae recovered between 2010 and 2015 were voluntarily collected from 33 general hospitals and confirmed by PCR. The species were identified by sequences of the 16S rDNA. Antimicrobial susceptibility was determined either by the disk diffusion method or by broth microdilution, and the carbapenem MICs were determined by agar dilution. Then, multilocus sequence typing and PCR-based replicon typing was carried out. Co-carried genes for drug resistance were identified by PCR and sequencing. The entire genomes of eight random selected NDM producers were sequenced. A total of 69 Klebsiella pneumoniae of 12 sequence types (STs), 34 Escherichia coli of 15 STs, 28 Enterobacter spp. (including one Enterobacter aerogenes), nine Citrobacter freundii, four Raoultella spp., and two Klebsiella oxytoca isolates produced either NDM-1 (n = 126), NDM-5 (n = 18), or NDM-7 (n = 2). The isolates co-produced CTX-M-type ESBL (52.1%), AmpCs (27.4%), additional carbapenemases (7.1%), and/or 16S rRNA methyltransferases (4.8%), resulting in multidrug-resistance (47.9%) or extensively drug-resistance (52.1%). Among plasmids harboring blaNDM, IncX3 was predominant (77.4%), followed by the IncFII type (5.8%). Genome analysis revealed inter-species and inter-strain horizontal gene transfer of the plasmid. Both clonal dissemination and plasmid transfer contributed to the wide dissemination of NDM producers in South Korea.